Beyond Textbook Instruction: Stories from ELT Teachers in Oman. Issue 3 (3rd July 2019) - Al-Issa, Ali
ABSTRACT: The government of the Sultanate of Oman actively promotes the value of English as a global lingua franca to support modernization and national economic growth. This policy, however, creates difficulties for many teachers, who find themselves implementing certain practices that conflict with a vision of English language teaching (ELT) that accords with humanist values. They find themselves adopting forms of instruction that reduce English to a matter of drills and skills. This essay draws on an inquiry that I facilitated with the help of four Student Teachers during their practicum. The inquiry involved asking them to keep reflective journals in an effort to place their teaching in a critical perspective exposing the contradictory nature of their professional situation. The journals show their struggle with the ELT status quo at their cooperating schools, while revealing their commitment to opening up educational opportunities for their students beyond what the curriculum prescribes.